Influenza seasonality and predominant subtypes of influenza virus in Guangdong, China, 2004-2012 - Lin, Jinyan (Pioneer Bioscience Publishing Company, 2013)
BACKGROUND: Influenza surveillance is carried out in Guangdong province, southern China. A better understanding of influenza seasonality and predominant Subtypes of influenza virus in Guangdong can help to improve evidence-based prevention and control strategies for influenza in the future. MATERIALS AND METHODS: There are three categories of influenza surveillance in Guangdong: Influenza-like Illness (ILI) Outpatient Surveillance, ILI Outbreak Surveillance and Influenza Virus Surveillance. This paper summarizes collected influenza surveillance data from January 2004 to December 2012 in Guangdong province. Time series analysis and “peak analysis” were performed to estimate seasonality and temporal trends of influenza activity. RESULTS: During the 9-year study period, a total of 37,571,582 outpatients had been recorded, in which 1,889,684 ILI cases had been reported. The provincial ILI visiting percentage peaked at 6-10%. A total of 107,115 respiratory specimens of ILI outpatients were collected, 17,454 (16.29%) of them tested for influenza virus were positive. Influenza virus peaks appeared in summer mostly with a median epidemic duration of 6 months. A total of 925 outbreaks recorded and 45,322 cases in which were affected. The majority of reported outbreaks (832 outbreaks, 90%) occurred in institutional settings. CONCLUSIONS: Influenza circulates periodically every year in Guangdong. Influenza activity had strong and clear seasonality with epidemic periods in summer for last decade. The presence of local unique seasonal pattern and its changes emphasizes the need to optimize timing of influenza vaccine delivery and other public health interventions.